2020
DOI: 10.3389/fped.2020.526969
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Involvement in Kawasaki Disease Is Much More Than Mere Coronary Arteritis

Abstract: Kawasaki disease (KD) is now a common cause of acquired heart disease in children. Coronary artery involvement is the most serious complication in children with KD. Several non-coronary complications have now been identified in this condition but these are often overlooked. Myocarditis is an integral component of KD and may be more common than coronary artery abnormalities. Pericardial involvement and valvular abnormalities have also been observed in patients with KD. KD shock syndrome is now being increasingl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 125 publications
(195 reference statements)
0
20
0
Order By: Relevance
“…Whittaker et al have shown that NT-pro-BNP levels were elevated in 83% patients, while troponins were increased in 68% patients [42]. 2D-echocardiography should be carried out for identification of myocarditis, pericarditis, valvular abnormalities and CAAs [48,56,57]. The electrocardiogram may show changes of myocardial strain.…”
Section: Laboratory Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Whittaker et al have shown that NT-pro-BNP levels were elevated in 83% patients, while troponins were increased in 68% patients [42]. 2D-echocardiography should be carried out for identification of myocarditis, pericarditis, valvular abnormalities and CAAs [48,56,57]. The electrocardiogram may show changes of myocardial strain.…”
Section: Laboratory Featuresmentioning
confidence: 99%
“…Cardiovascular complications are the most prominent manifestations in patients with MIS-C. Cardiac biomarkers including NT-pro-BNP and troponin levels are extremely high compared to historical KD cohorts and indicate heart failure and myocardial damage in MIS-C. Symptomatic myocarditis has been reported in 40-80% of patients with MIS-C [7,8,11,40]. In contrast, symptomatic myocarditis is seen in < 5% of patients with KD [46][47][48]. Pouletty et al reported that severe disease requiring intensive care due to myocarditis was seen in approximately 50% of patients with MIS-C and the risk was higher in older children [8].…”
Section: Cardiovascular Complicationsmentioning
confidence: 99%
“…Symptomatic myocarditis was found in 40–80% of patients with MIS-C [ 13 , 14 ]. In contrast, symptomatic myocarditis is seen in < 5% of KD patients [ 15 17 ]. Pouletty et al documented the presence of severe myocarditis in approximately 50% of MIS-C patients with higher risk in older children [ 13 ].…”
Section: Research Strategymentioning
confidence: 99%
“…This disease with the effect on medium-sized arteries manifests as persistent fever, erythema of the lips and oral mucosa, bilateral non-purulent conjunctivitis, skin rashes, swelling and redness of the hands and feet, and cervical lymphadenopathy and usually follows with a short period of respiratory or gastrointestinal symptoms [ 1 , 4 , 5 ]. As cardiac complications are the most concerning ones, it is essential to adopt efficient methods to diagnose and treat this self-limited disease [ 9 ]. If no treatment is performed, the development of coronary artery aneurysms (CAAs) may observe in 15–25% of children with KD [ 10 ].…”
Section: Introductionmentioning
confidence: 99%